1998
DOI: 10.1002/(sici)1097-0142(19980415)82:8<1535::aid-cncr16>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary heterologous carcinosarcoma (Metaplastic carcinoma) of the urinary bladder

Abstract: On the basis of the current series and a review of 55 reports from the literature, primary heterologous carcinosarcoma of the urinary bladder proved to be a highly malignant type of neoplasm occurring predominantly in elderly males that was most often in an advanced stage at presentation and rapidly became lethal. Histogenetically, some heterologous carcinosarcomas should be regarded as a variant of sarcomatoid carcinoma (metaplastic carcinoma) that shows prominent heterologous differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Völker et al (8) proposed that carcinosarcomas may originate from a common pluripotent progenitor cell that is capable of undergoing epithelial and mesenchymal differentiation. Perret et al (9) proposed that certain carcinosarcomas should be regarded as a variant of sarcomatoid carcinoma (metaplastic carcinoma) that shows prominent heterologous differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Völker et al (8) proposed that carcinosarcomas may originate from a common pluripotent progenitor cell that is capable of undergoing epithelial and mesenchymal differentiation. Perret et al (9) proposed that certain carcinosarcomas should be regarded as a variant of sarcomatoid carcinoma (metaplastic carcinoma) that shows prominent heterologous differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, due to the age of the patient and the history of previous pelvic surgery, a laparoscopic radical resection of the right kidney and ureter was performed. Previous studies have reported very poor prognoses for carcinosarcoma, with a median cancer-specific survival time of approximately one year (6,9,20). One half of patients are reported to succumb within approximately one year of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many series emphasize the importance of stage for the prognosis [1, 3, 4]. Half of patients die within 1 year from the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Half of patients die within 1 year from the diagnosis. However, in a case series study none of 8 patients with pT1 disease died of the disease, although followup was incomplete in 3 of them [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Ever since first described in 1865, this kind of tumor has been reported in almost every organ such as breast, urinary bladder, uterus, liver, larynx, gallbladder, lungs and skin (2)(3)(4)(5)(6)(7)(8)(9). However, controversy in its pathogenesis and treatment still remains.…”
Section: Introductionmentioning
confidence: 99%